1988
DOI: 10.1007/bf01753576
|View full text |Cite
|
Sign up to set email alerts
|

Differential permeability of lymphatic and blood vessels in determining the route of metastasis as demonstrated by indirect lymphography

Abstract: Indirect mammo-lymphography with serial radiograms was made on rats bearing three established rat mammary carcinomas (SMT-2A, TMT-50, MT-W9B), with the water-soluble contrast medium, Iotasul. In the lymphogenously metastasizing SMT-2A, fine lymphatic sprouts from the tumor were seen converging into an afferent lymph vessel that was extending toward a metastatic regional lymph node, in 15-30 min. For 45 min, the dye remained localized in the primary tumor with no other vascular structures or viscera visible unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lymphatic vessels (LV) in the tumor microenvironment are primarily considered as a route of tumor dissemination 17 . LV are leaky compared to blood vessels, because they are only sparsely covered with pericytes and smooth muscle cells 18 . Thus in certain types of cancers such as in breast cancer, metastasis occurs preferentially through the lymphatic vasculature compared to the blood vessel mediated spreading 19 20 .…”
mentioning
confidence: 99%
“…Lymphatic vessels (LV) in the tumor microenvironment are primarily considered as a route of tumor dissemination 17 . LV are leaky compared to blood vessels, because they are only sparsely covered with pericytes and smooth muscle cells 18 . Thus in certain types of cancers such as in breast cancer, metastasis occurs preferentially through the lymphatic vasculature compared to the blood vessel mediated spreading 19 20 .…”
mentioning
confidence: 99%
“…Not surprisingly, studies found that peritumoral and intratumoral lymphatic microvessels are also disorganized and lack drainage function (Isaka et al, 2004; Padera et al, 2002). This structural irregularity might contribute to their susceptibility to invading malignant cells (Kim et al, 1988). …”
Section: Biological Background and Hypothesesmentioning
confidence: 99%